2021
DOI: 10.1097/md.0000000000027474
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of delayed percutaneous coronary intervention for patients with ST-segment elevation myocardial infarction

Abstract: The best time window of percutaneous coronary intervention (PCI) is within 12 hours for ST-segment elevation myocardial infarction (STEMI). However, there is limited evidence about the proper time of PCI for delayed STEMI patients.From June 2014 to June 2015, a total of 268 patients receiving PCI with second-generation drug-eluting stent in a Chinese hospital after 3 days of STEMI onset were enrolled in this retrospective study, who were divided into the early group (3-14 days) and the late group (>14 days). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, Li et al found that in patients with STEMI 12–72 h after symptom onset and with spontaneous reperfusion of the infarct-related artery, delayed PCI showed a higher procedural success rate without increasing in-hospital and long-term mortality [ 23 ]. A propensity matched study revealed that patients with STEMI who underwent early PCI (defined in the study as 3-14d after onset) had a higher risk of recurrent MI than patients with STEMI who underwent late PCI (defined in the study as more than 14d after onset) [ 24 ]. The Occluded Artery Trial (OAT) study also showed that in patients with occlusion of the infarct-related artery 3-28d after MI and high-risk criterion, routine PCI did not reduce the incidence of death, reinfarction, or heart failure, and there was a trend toward excess reinfarction compared with optimal medical therapy alone [ 25 ], and this result was not affected by patient risk level or extended follow-up [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Li et al found that in patients with STEMI 12–72 h after symptom onset and with spontaneous reperfusion of the infarct-related artery, delayed PCI showed a higher procedural success rate without increasing in-hospital and long-term mortality [ 23 ]. A propensity matched study revealed that patients with STEMI who underwent early PCI (defined in the study as 3-14d after onset) had a higher risk of recurrent MI than patients with STEMI who underwent late PCI (defined in the study as more than 14d after onset) [ 24 ]. The Occluded Artery Trial (OAT) study also showed that in patients with occlusion of the infarct-related artery 3-28d after MI and high-risk criterion, routine PCI did not reduce the incidence of death, reinfarction, or heart failure, and there was a trend toward excess reinfarction compared with optimal medical therapy alone [ 25 ], and this result was not affected by patient risk level or extended follow-up [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] However, another study found similar efficacy and long-term outcome in early PCI (3–14 days) and late PCI (>14 days) using a second drug-eluting stent. [ 19 ] Therefore, late PCI is considered in our patients without documented follow-up to assess the long-term outcome. Latecomers post-MI with total occlusion in the coronary angiogram were treated by PCI as a treatment strategy in our center.…”
Section: Discussionmentioning
confidence: 99%